2021
DOI: 10.3390/ijerph18041998
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of Direct and Meta Versions of the Coach–Athlete Relationship Questionnaire (ArCART-Q) in the Arabic Language: Their Relationship to Athlete’s Satisfaction with Individual Performance

Abstract: Background: The first aim of this study is to achieve validation of the direct and meta-perspective versions of the Coach–Athlete Relationship Questionnaire in the Arabic language, and the second aim of this study is to determine the quality of the coach-athlete relationship to athlete’ satisfaction with individual performance according to sport participation type, sport duration, and sport achievement. Methods: A total of 259 athletes with a mean age of 22 years were recruited from various athletic clubs in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Overall, the original structure of the instrument with 11 items and three dimensions (closeness, commitment, and complementarity) was maintained, corroborating results from previous research that was carried out in other cultures. 22,30,54,55 Based on the present results, the instrument presents satisfactory internal consistency, factor structure, factor invariance, sensitiveness to individual characteristics variation, and nomological validity to assess the athlete-coach relationship according to the athletes’ perspective.…”
Section: Discussionmentioning
confidence: 72%
“…Overall, the original structure of the instrument with 11 items and three dimensions (closeness, commitment, and complementarity) was maintained, corroborating results from previous research that was carried out in other cultures. 22,30,54,55 Based on the present results, the instrument presents satisfactory internal consistency, factor structure, factor invariance, sensitiveness to individual characteristics variation, and nomological validity to assess the athlete-coach relationship according to the athletes’ perspective.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to prior research findings in which sex invariance was not established (e.g., Ahmad et al, 2021 ; Jowett & Clark-Carter, 2006 ; Jowett & Nezlek, 2012 ), we actively sought to address this issue and can confidently assert that, in this Portugese population, the model held equal validity and consistency for both male and female athletes, and that factors shared identical structures and interpretations in these two samples. This aspect is especially noteworthy because existing literature has already unveiled certain distinctions between men and women concerning these variables.…”
Section: Discussionmentioning
confidence: 94%
“…A validation study of direct and meta-perspective versions of the CART-Q translated to Arabic showed significant sex differences in satisfaction and CART-Q scores. Female athletes had significantly higher scores in all subdimensions, likely influenced by cultural norms and female coaches in Kuwait ( Ahmad et al, 2021 ). Hence, when assessing cognitive constructs such as perceived interpersonal behaviors of athletes’ regard to coaches, Rodrigues et al (2020) emphasized the importance of conducting research within specific cultural and contextual frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The CART-Q has been achieved by being a worldwide measurement tool. The British [47], Greek [50], Arabic [51], Chinese [52], Brazilian [53], Belgian [54], and Turkish [55] versions have been adapted to these cultures. Furthermore, the construct of the CART-Q has been demonstrated to be a useful tool for measuring the coach-athlete relationship in all these cultures.…”
Section: Introductionmentioning
confidence: 99%